The effect of hepatotropic virus B and C on the degree of hyperglycemia and iron overload and the correlation between hyperglycemia and iron overload in hepatitis patients - Kadhem, Zainab Ali (University of Thi-Qar Journal of Science, 2013)
Aims: This study was design to evaluate the effect of hepatotropic virus’s types on the degree of hyperglycemia and iron overload and the correlation between hyperglycemia and iron overload in patients with hepatitis B and C.Methods: Fifty patients infected with hepatitis B and C virus admitted in Al-Hussein teaching hospital /Thi- Qar governorate, along with fifty healthy individual as a control group for comparison purposes. The study period was from April 2011 to July 2012.Results: Of these fifty patients 47 were male (94%) and 3 were female (6%), out of which 39 (78 %) had viral hepatitis B infection and 11 (22 %) had viral hepatitis C infection. The levels of blood glucose (209.52 ± 55.11 mg/dL) and iron (386. 65 ± 95.62 μg/dL) were significantly elevated in hepatitis patients as compare with the control group (73.22 ± 8.30 mg/dL) and (154.15 ± 11.18 μg/dL) respectively. The concentration of blood glucose was 210.39 ± 52.37 mg/dL and 195.84 ± 64.77 mg/dL in hepatitis B and C respectively, there is no significant different in blood glucose between HBV and HCV patients. The concentration of iron was390.88 ± 114.82 μg/dL and 385.27 ± 89.87 μg/dL in hepatitis B and C respectively, there is no significant different in blood iron between HBV and HCV patients. There is a positive correlation between blood glucose and iron in hepatitis patients. Conclusion: The fifty hepatitis patients associated with severe hyperglycemia and iron overload and there is no effect of hepatotropic virus.